Energy management program for use of induction motors based on efficiency prediction - Phumiphak, T.; Kedsoi, T.; Chat-Uthai, C. (My University, 2005)
Electric drive systems are currently responsible for the largest part of the electricity consumption. As the cost of energy increases, it is increasingly more important to remove the inefficient induction motors from operation. This paper proposes an energy management program that can help the plants to determine how much saving will be achieved by using more efficient motors. This paper focuses on the use of motor field efficiency estimation of motors without the removal of motor from service and without the output power measurement, and the use of motor efficiency prediction based on the manufacturer information. The motor efficiency evaluations are obtained from the equivalent circuit method. The test results indicate that this program is a tool of accurate economic analysis for the purchase scenario. As a result, it is possible to conduct on-site energy audits of existing motors in order to determine the potential savings and payback period with great confidence.
Keywords: Efficiency prediction; Equivalent circuit method; Field efficiency; Induction motors; On-site energy audits